Antiinflammation constituents from Curcuma zedoaroides. (15th August 2018) - Tungcharoen, Pattreeya; Wattanapiromsakul, Chatchai; Tansakul, Pimpimon; Nakamura, Seikou; Matsuda, Hisashi; Tewtrakul, Supinya
Abstract : Curcuma zedoaroides, a Zingiberaceae species, has been used for snake bite antidote and wound care in Thailand. Seven compounds were isolated from the bioactive chloroform extract consisted of one new guaiane sesquiterpene lactone, 5‐epiphaeocaulisin A (4 ) and one new diarylheptanoid, 1, 2, 3, 5‐tetrahydroxy‐1‐(4‐hydroxy‐3‐methoxyphenyl)‐7‐(4‐hydroxyphenyl) heptane (7 ), together with five known guaiane‐type sesquiterpene lactones including gweicurculactone (1 ), zedoalactone B (2 ), phaeocaulisin C (3 ), zedoalactone H (5 ), and zedoalactone E (6 ). The antiinflammation was investigated on NO and TNF‐α production using RAW264.7 cells. In addition, the expressions of genes involved in inflammation including iNOS, COX‐2, and TNF‐α were assessed. The results found that Compounds1 –7 presented their antiinflammation against NO production. The most potential effects were demonstrated on Compounds1 and7 with IC50 of 27.3 and 32.6 μM, respectively. Although, Compounds1 and7 did not inhibit TNF‐α production, their suppression on iNOS and COX‐2 mRNA expression were revealed. These results support the ability of chloroform fraction, Compounds1 and7 on antiinflammation, whereas others exhibited moderate and mild effect.